STRENGTHENING LOCAL CULTURE AWARENESS IN TEACHING WRITING; A CASE STUDY AT MUHAMMADIYAH UNIVERSITY OF PAREPARE - Salasiah, Salasiah; Khairil, Khairil (Elite : English and Literature Journal, 2016)
AbstractLocal culture content approach in education has long been discussed and there are still some arguments on its position in education. Regardless its issues, as a teacher I believed that local culture has significant position in education. Therefore, in my teaching, I always attach culture value in it as a shape of my awareness toward it. This study based on a personal experience in teaching writing for beginner students at English department of Muhammadiyah University of Parepare. The study explores the interference of local culture knowledge in affecting students’ idea forming in class of writing. The participant of the study was the 2nd semester students; class A and B in 2012/2013. The study design applied was case study. It revealed in the study that the use of local culture based material in writing can ease students in mapping their writing ideas as well as reinforcing their awareness toward their local culture. Students enjoyed writing as the material given is familiar to them while at the same time they can strengthen their local culture awareness. Also reinforcing local culture knowledge in teaching English can help widen student’s knowledge on writing.AbstrakPenguatan Budaya Lokal dalam Pengajaran Writing; Suatu Studi Kasus di Universitas Muhammadiyah Parepare. Pendekatan konten budaya lokal dalam pendidikan lama telah dibahas dan masih ada beberapa argumen pada posisi dalam pendidikan. Terlepas dari isu-isu yang, sebagai guru, saya percaya bahwa budaya lokal memiliki posisi penting di bidang pendidikan. Oleh karena itu, dalam mengajar saya, saya selalu melampirkan nilai budaya di dalamnya sebagai bentuk kesadaran saya ke arah itu. Studi ini didasarkan pada pengalaman pribadi dalam mengajar menulis untuk pemula siswa di Departemen bahasa Inggris dari Universitas Muhammadiyah kota Pare. Studi mengeksplorasi gangguan pengetahuan budaya lokal dalam mempengaruhi siswa ide membentuk di kelas menulis. Peserta studi adalah mahasiswa semester 2; kelas A dan B di 2012/2013. Desain studi yang diterapkan pada studi kasus. Itu mengungkapkan dalam studi bahwa penggunaan bahan budaya lokal dalam menulis dapat memudahkan siswa dalam pemetaan ide-ide menulis mereka serta memperkuat kesadaran mereka terhadap budaya lokal mereka. Siswa menikmati menulis sebagai materi yang diberikan akrab bagi mereka sementara pada saat yang sama mereka dapat memperkuat kesadaran budaya lokal mereka. Juga memperkuat pengetahuan budaya lokal dalam mengajar bahasa Inggris dapat membantu memperluas pengetahuan siswa menulis.